Approaches to Construction Waste Management in Malaysia - Othuman Mydin, M.A.; Khor, J.C.; Md. Sani, N. (EDP Sciences, 2014)
The concept of construction waste management was introduced a long time ago but the effort of waste minimization has, for the most part, merely been observed and not practiced. Additionally, an increasing allocation of landfills has indicated a growing production of waste. However, the allocation of funding or skills for the prevention of waste has been scarce as waste minimization has not been given enough attention. One such example is the undertaking of different stages of construction, which often does not account for future problems in construction waste. Hence, this study is intended to investigate common waste management practices on construction sites in Malaysia. As part of this investigation, site observations and questionnaires were conducted to collect information from the respondents. Comprehensive literature reviews also helped to understand the latest norms as well as previous practices in waste management. The results reflected that certain areas of knowledge and implementation showed great gaps with the same mistakes appearing frequently, pointing to the conclusion that known causes of excess waste are often not rectified and suggestions for improvement are not fully incorporated in standard practices.